Scientific and Information Literacy of High School Students - Kuni Mawaddah; Susriyati Mahanal; Abdul Gofur; Siti Zubaidah (Pascasarjana Universitas Negeri Malang (UM), 2020)
Abstract: This study aims to analyze the level of scientific, information literacy, and determine the relationship of scientific and information literacy. This quantitative descriptive survey has a sample of 145 high school students, selected by random sampling. Scientific and information literacy instruments have been validated by the experts and tested on 25 students who have studied Bacteria. The majority of scientific and information literacy are at the developing level. There is a positive relationship between scientific and information literacy for high school students. Based on these results, efforts are needed to empower scientific and information literacy for high school students by applying innovative learning models.Key Words: scientific literacy; information literacy; high school studentsAbstract: Penelitian ini bertujuan untuk menganalisis tingkat literasi sains, literasi informasi, dan mengetahui hubungan literasi sains dan literasi informasi. Penelitian deskriptif kuantitatif survei ini mengambil sampel 145 siswa SMA yang dipilih dengan random sampling. Pengumpulan data dengan instrumen literasi sains dan literasi informasi yang telah divalidasi oleh validator dan diujikan pada 25 siswa yang telah mempelajari materi Bakteri. Mayoritas literasi sains dan literasi informasi berada pada tingkat developing. Terdapat hubungan positif antara literasi sains dan literasi informasi siswa SMA. Berdasarkan hasil tersebut, diperlukan upaya peningkatan literasi sains dan literasi informasi siswa SMA misalnya dengan penerapan model pembelajaran inovatif.Kata kunci: literasi ilmiah; literasi informasi; siswa SMA